On the use of Synthetic Indexes Based on Multi-Criteria Decision Making to Study the Efficiency of Teachers - Ruiz-Mora, Ana Belén; Marcenaro-Gutiérrez, Óscar David; Luque-Gallego, Mariano (Springer, 2022)
Efficiency in education constitutes a dimension of the quality of education and gaining knowledge about the teachers’ efficiency can contribute to improving the learning achieve- ment of students. The main purpose of this paper is to evaluate the teachers’ efficiency in order to determine which policies should be promoted in the future to reach a teach- ing environment enabling the teachers to be efficient. That is, we want to have a bet- ter insight about how to distribute the available resources to improve key factors of the teaching-learning context that are desirable to let them to achieve efficiency. To this aim, we measure the teachers’ efficiency from a wide multi-criteria decision making sense. We consider all the significant variables at the same importance level, assuming that efficient teachers are those achieving the best possible values for all of them simultaneously. Data from TIMSS and PIRLS 2011 for fourth-grade Spanish teachers in reading, mathematics and science are used. Firstly, three synthetic indexes (weak, strong and mixed) are built using a multi-criteria decision making approach that incorporates desirable ranges for the variable values. This allows us to know which teachers are performing better, within or worse than the desired limits. Afterward, a second stage analysis is performed to investi- gate the extent to which the controllable variables are determinant in the teachers’ rankings associated with these indexes. With all of this, key variables for being in the best/worst ranking positions are identified, which lets us better know which measures should be taken to promote efficiency in teaching.
Keywords: Toma de decisiones; Efficiency; Teachers; Synthetic index; Multi-criteria decision making